Joint Cruise 1-2 2018: Cruise Report - Ingvaldsen, Randi; Bluhm, Bodil; Aberle-Malzahn, Nicole; Amundsen, Rita; Van Ardelan, Murat; Bagøien, Espen; Bratbak, Gunnar; Bratrein, Marius; Chierici, Melissa; Descoteux, Raphaelle; Dietrich, Ulrike; Divine, Dimitry; et al. (The Nansen Legacy Report Series, 2020)
Joint Cruise 1-2 with R/V Kronprins Haakon addressed objectives of RF1, RF2 and RF3 on the Nansen Legacy main transect in open water and within the sea ice. The focus was on comparing the state of the physical, chemical and biological conditions in the southern and northern parts of the study area. Given this was the first research cruise on the vessel, the cruise also focused on testing gear and equipment, and establishing routines for gear deployments, collaboration, data management and storing.